2016
DOI: 10.1097/aog.0000000000001248
|View full text |Cite
|
Sign up to set email alerts
|

Successful Oocyte Cryopreservation in Reproductive-Aged Cancer Survivors

Abstract: Oocyte cryopreservation is now a feasible fertility preservation option for reproductive-aged patients with cancer who require gonadotoxic therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 25 publications
(40 reference statements)
2
32
1
2
Order By: Relevance
“…Of note, the oldest patient of this cohort (41 years old) cryopreserved 10 oocytes but obtained no euploid embryos after fertilization and did not undergo embryo transfer. In 2016 Druckenmiller et al [69] reported a 44% live birth rate per embryo transfer after thawing/warming of oocytes in 10 patients with a 10 median age of 32 years. Oocyte survival rate and fertilization rate were similar to the ones obtained in patients without cancer at the same institution (live birth rate of 33% in non-cancer patients of less than 43 years).…”
Section: Efficacy Of Oocyte Cryopreservation In Cancer Patientsmentioning
confidence: 99%
“…Of note, the oldest patient of this cohort (41 years old) cryopreserved 10 oocytes but obtained no euploid embryos after fertilization and did not undergo embryo transfer. In 2016 Druckenmiller et al [69] reported a 44% live birth rate per embryo transfer after thawing/warming of oocytes in 10 patients with a 10 median age of 32 years. Oocyte survival rate and fertilization rate were similar to the ones obtained in patients without cancer at the same institution (live birth rate of 33% in non-cancer patients of less than 43 years).…”
Section: Efficacy Of Oocyte Cryopreservation In Cancer Patientsmentioning
confidence: 99%
“…Mature oocytes can be effectively cryopreserved using a vitrification method and the success rates of post-thaw fertilization and pregnancy rates have approached those with fresh oocytes in young patients, though success rates with frozen embryos may still be better[46,47]. Oocyte cryopreservation success rates vary depending on age, number of oocytes frozen and the freezing protocol.…”
Section: Fertility Preservation Options For Breast Cancer Patientsmentioning
confidence: 99%
“…Several fertility preservation approaches are available, including cortical or whole ovary cryopreservation and immature oocyte cryopreservation, to store oocytes or embryos for future use (Anderson & Wallace, 2011 (Druckenmiller et al, 2016;Garcia-Velasco et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However currently, embryo and mature oocyte cryopreservation following controlled ovarian stimulation (COS) are the only techniques endorsed by the American Society of Reproductive Medicine with other methods still considered to be investigational (Andersen & Ezcurra, 2014; Ethics Committee of American Society for Reproductive Medicine, 2013). Observational studies reporting on number of oocytes stored for future use have shown satisfactory results (Druckenmiller et al, 2016;Garcia-Velasco et al, 2013).…”
Section: Introductionmentioning
confidence: 99%